Analyzing Hong Kong’s Inbound Tourism: The Impact of the COVID-19 Pandemic - Tsui WHK; Fu X; Chen T; Lei Z; Wu H (Elsevier)
This study empirically investigates the determinants and drivers of Hong Kong’s inbound tourism using data from January 2019 to December 2020. Five of Hong Kong’s major regional tourism source markets are selected: Japan, Malaysia, the Philippines, Singapore, and South Korea. Our empirical results suggest that the COVID-19 pandemic has had significant negative impacts on the tourism and aviation sectors in Hong Kong that are asymmetric in the source and destination countries. In addition, international travel control imposed by the Hong Kong government is often defined according to the pandemic situation in the tourism source countries, Hong Kong’s inbound visitor volume is also significantly affected by the Hong Kong government’s response to COVID-19 infection cases in the tourism origin markets. Our empirical results also suggest that the flying distance to Hong Kong and high tourism costs in Hong Kong reduced visitor arrival demand, whereas increased aviation services and tourism market potential contributed to tourism growth. These results suggest that the tourism industry and government agencies should cooperate to recover when the pandemic is under good control, so that Hong Kong will be regarded as a preferred and safe destination for travelers and visitors. Our study emphasizes the complementarity between pandemic control and tourism recovery. Pandemic control involves extra tests and quarantine requirements on passengers, more vigorous border control. These operational and associated financial requirements call for government support to the tourism and aviation sectors in the early stage of recovery to create a positive feedback loop.
Keywords: Aviation; COVID-19; Hong Kong; Tourism; 1117 Public Health and Health Services; 1507 Transportation and Freight Services; 1701 Psychology